2015
DOI: 10.1016/j.joca.2015.02.581
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the renin-angiotensin system introduces osteoarthritis

Abstract: In 2013, we reported that the local renin-angiotensin system (RAS) can modulate the hypertrophic differentiation of chondrocytes. Abstracts / Osteoarthritis and Cartilage 23 (2015) A82eA416 A320

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 25 In addition, renin-angiotensin system could regulate hypertrophic differentiation of chondrocytes. 26 Furthermore, another earlier study reported that AGT precursor in synovial fluid participated in the mechanism of OA by inhibiting proteinase activities. 27 In this study, AGT was also a hub node in PPI network, regulated by SPI1.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In addition, renin-angiotensin system could regulate hypertrophic differentiation of chondrocytes. 26 Furthermore, another earlier study reported that AGT precursor in synovial fluid participated in the mechanism of OA by inhibiting proteinase activities. 27 In this study, AGT was also a hub node in PPI network, regulated by SPI1.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence had demonstrated that local renin-angiotensin system components expressed particularly in hypertrophic chondrocytes and did not in hyaline chondrocytes (25). Recently, Yamagishi et al revealed that activation of the renin-angiotensin system may introduce OA (26). Evidence had shown that an ACE inhibitor (Ramipril) could improve vascular function in patients with rheumatoid arthritis (27).…”
Section: Gene Changementioning
confidence: 99%